2020
DOI: 10.3389/fonc.2020.01284
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Study Comparing Efficacy and Toxicity of Weekly vs. 3-Weekly Induction Chemotherapy in Locally Advanced Head and Neck Squamous Cell Carcinoma

Abstract: Background: Head and Neck Cancer is a major public health problem in India, majority of which are lifestyle related, male predominant requiring dedicated infrastructure and human resource. The 5-year survival is 59% for all stages combined and only 45% in patients with locally advanced inoperable head and neck cancer using current chemoradiation schedules. Chemotherapy agents administered in the induction or concurrent setting comprise of taxanes (Docetaxel, paclitaxel), platinum compounds (Cisplatin, carbopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…To decrease TPF toxicity without changing efficacy, modified schedule of TPF has been proposed. But, data from randomized trial are currently limited and results mixed [133,134]. Better selection tools to identify patients who will benefit from TPF induction remain needed.…”
Section: Discussionmentioning
confidence: 99%
“…To decrease TPF toxicity without changing efficacy, modified schedule of TPF has been proposed. But, data from randomized trial are currently limited and results mixed [133,134]. Better selection tools to identify patients who will benefit from TPF induction remain needed.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have modified the conventional induction treatment plan using a 1-day slow infusion of 5FU as per institutional logistics. There have been attempts to use a modified TPF regimen to decrease its toxicity without altering the efficacy, but the available data are scarce and mixed [16,17]. Accelerated repopulation is also a noted radiobiological concern in head-and-neck squamous cell cancer, to address this issue, we started CTRT 2 weeks after completion of induction TPF, while several trials used a 3-5-week gap.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, minimizing adverse effects during treatment is an important goal for clinical oncologists. In recent years, increasing evidence has indicated that weekly chemotherapy has similar efficacy and lower toxicity than triweekly regimens for many types of cancers ( Schuette et al, 2005 ; Dessai et al, 2016 ; Tousif et al, 2020 ). Multiple studies have compared the outcomes of weekly and triweekly cisplatin concurrent chemoradiotherapy (CCRT) in advanced head and neck squamous cell carcinoma (HNSCC) ( Espelia et al, 2012 ; Geiger et al, 2014 ; Tsan et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%